2019
DOI: 10.1103/physrevb.99.195112
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal string order parameter in the S=12 Kitaev-Heisenberg ladder

Abstract: We study the spin-1 2 Kitaev-Heisenberg (KJ) model in a two-leg ladder. Without a Heisenberg interaction, the Kitaev phase in the ladder model has Majorana fermions with local Z2 gauge fields, and is usually described as a disordered phase without any order parameter. Here we prove the existence of a non-local string order parameter (SOP) in the Kitaev phase which survives with a finite Heisenberg interaction. The SOP is obtained by relating the Kitaev ladder, through a non-local unitary transformation, to a o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…We denote the total number of sites in the strip by N . This geometry has recently been used to study the Kitaev-Heisenberg model 49 , where it was found that its phase diagram displays a striking similarity with that of the 2D honeycomb lattice. Further rationale for this choice of geometry is discussed in the SI.…”
Section: R 1 I O W W N C a R N 4 M M V N O A W M H A A G W E 8 W Y U ...mentioning
confidence: 99%
“…We denote the total number of sites in the strip by N . This geometry has recently been used to study the Kitaev-Heisenberg model 49 , where it was found that its phase diagram displays a striking similarity with that of the 2D honeycomb lattice. Further rationale for this choice of geometry is discussed in the SI.…”
Section: R 1 I O W W N C a R N 4 M M V N O A W M H A A G W E 8 W Y U ...mentioning
confidence: 99%
“…den Nijs and Rommelse first showed that the SOP witnesses the hidden Néel order of the Haldane phase of the spin-1 AKLT model [76]. More recent work has extended the use of SOPs in the analysis of topological phases also to bosonic and fermionic systems [77][78][79][80][81]. Recently, within the context of high T c superconductivity, SOPs have been used to theoretically study the topological phases diagram of the t − J model [82].…”
Section: String Order Parametermentioning
confidence: 99%
“…Therefore, investigations in reduced dimensionality, i.e., in one-dimensional (1D) systems, can be useful and valuable to better understand the 2D physics, since there are more controllable theoretical tools in 1D [34][35][36][37][38][39][40][41][42] . Recently, there has been a series of theoretical works on the phase diagrams of quasi-1D generalized Kitaev models [43][44][45][46][47][48][49][50][51][52][53] . A plethora of interesting phases has been found, including emergent conformal invariance, Luttinger liquid phases, magnetically ordered phases, nonlocal string orders, and spin liquids.…”
Section: Introductionmentioning
confidence: 99%